Implementasi Peran BKPSDM Terhadap Kedudukan Tenaga Guru Non-ASN Dalam Penataan Pegawai Pemerintah Dengan Perjanjian Kerja di Kota Tangerang - Rizki, Muhamad; Nurikah, Nurikah; Kusumaningsih, Rila (Primagraha Law Review, 2025)
The services provided by the regional government in the appointment of honorary workers in the education sector, especially the appointment of non-ASN teachers to become PPPK are still colored by various obstacles and conditional interests, in Article 66 of Law Number 20 of 2023 non-ASN employees are required to complete their arrangements no later than December 2024. So, since this Law came into effect, Government Agencies are prohibited from appointing non-ASN employees or other names other than ASN Employees. The research method used is empirical juridical and the research specifications used are analytical descriptive. The results of this study indicate that the Tangerang City BKPSDM is currently arranging and determining the formation of non-ASN employees to take part in the PPPK selection, there are 5,186 non-ASN employees who will take part in PPPK in 2024. The conclusion in the arrangement of non-ASN workers, the Tangerang City government through the BKPSDM office does lack workers to carry out its duties, so then there is PPPK whose arrangement must be completed in 2024.